Development and characterization of biodegradable antimicrobial packaging films based on polycaprolactone, starch and pomegranate rind hybrids. (December 2018) - Khalid, Saud; Yu, Long; Feng, Mingyue; Meng, Linghan; Bai, Yuting; Ali, Amjad; Liu, Hongsheng; Chen, Ling
Highlights: PCL/starch/pomegranate rind hybrids were fabricated using extrusion technique. Pomegranate rind acted as antimicrobial and reinforcing agent. Starch triggered and enhanced the release of polyphenols. Films demonstrated potential as antimicrobial packaging material. Abstract: Polycaprolactone (PCL)/starch/pomegranate rind (PR) hybrids were developed for antimicrobial packaging applications. PR was used, for the first time, as an antimicrobial compound and was incorporated directly in PCL matrix, without the extraction of any active compound from the fruit rind. The PCL-based antimicrobial films were fabricated using extrusion technique. It was observed that PCL/PR films demonstrated reasonably good antimicrobial activity at higher concentration of active compound. Addition of starch not only lowered the cost but also improved the rigidity of PCL matrix. Adding to this, starch enhanced the antimicrobial activity of PR, and provided a releasing channel for the delivery of polyphenols by attenuating the interactions between PCL and PR. Since all the materials used in this work are biodegradable and food contactable, it is expected that the developed material can be employed as food-grade antimicrobial packaging material.